Speech Act Use in Jokowi Political Communication during The Press Conference of The State Visit in Moskow - Gabriel Fredi Daar; Fransiskus Jemadi (English Department of Faculty of Tarbiyah and Teacher Training, 2023)
Concern about global conditions due to war, famine, and disease prompted President Jokowidodo to make a state visit to Russia and Ukraine, the two largest exporters of fertilizer and wheat in the world. This study aims to analyze the speech act of Jokowidodo's press statement during a state visit to Moscow on June 30, 2022. This research is a qualitative descriptive study. The data was obtained by observing the video of Jokowi's press statement during a state visit to Moscow. The transcribed data were then grouped according to the order in which the press conference was delivered. The data were analyzed using Austin's speech act theory (1962) and Searle's (1979). Research shows that there are three types of speech acts in Jokowi's press statement, expressive speech acts, assertive speech acts (affirming and informing), and directive speech acts (influence, invite and convince). Although not explicitly stated, the speech act of Jokowi's press statement has a noble purpose and goal: to encourage countries that are in conflict to resolve conflicts by peaceful resolution.